PERAN KELUARGA, PENDIDIKAN, PERILAKU WIRAUSAHA DAN TRAIT KEPRIBADIAN TERHADAP KARAKTER KEWIRAUSAHAAN LULUSAN PERGURUAN TINGGI - Welan Mauli Angguna; Claudya Nurcahaya; Risanita Fardian Farid; Nurul Fadhillah Khair (Equivalent : Journal of Economic, Accounting and Management, 2023)
Unemployment in Indonesia is 12% dominated by university graduates (bachelor/diploma), while to become a developed country in 2045 it is necessary to achieve an entrepreneurial ratio of 4%. To achieve this ratio, the government encourages tertiary institutions to direct graduates to become entrepreneurs. Efforts to foster this interest in entrepreneurship also need to be facilitated by campus understanding regarding the entrepreneurial character of students, so that entrepreneurship programs can be carried out effectively by taking into account the personal characteristics of students. This study aims to examine the influence of personality traits on entrepreneurial character, and to test entrepreneurial character in predicting entrepreneurial behavior in Indonesian higher education graduates. This study was tested using a non-experimental quantitative method through a survey of 69 higher education graduates of which 42% were entrepreneurs. Entrepreneurial character was tested through 22 items of the Entrepreneurial Character Scale (Husna, Zahra & Haq, 2018), while the conscientiousness personality trait was tested using the Language version of the Ten Item Personality Inventory by Gosling (Akhtar, 2018). The results of the study show that entrepreneurial character can be significantly explained by the conscientiousness personality trait by 22% (p≤0.05). Entrepreneurial character is related to entrepreneurial behavior and family characteristics (having entrepreneurial parents) among university graduates in Indonesia, but the entrepreneurial education factor is not significantly related to entrepreneurial character. Further studies are suggested to test more about Entrepreneurship Education in predicting entrepreneurial behavior and the effectiveness of Entrepreneurship Education in fostering entrepreneurial interest and behavior. Abstrak Pengangguran di Indonesia sebesar 12% didominasi oleh lulusan perguruan tinggi (sarjana/diploma), sedangkan untuk menjadi negara maju di 2045 perlu tercapai rasio kewirausahan sebesar 4%. Untuk mencapai rasio tersebut, pemerintah mendorong perguruan tinggi untuk mengarahkan lulusan untuk menjadi wirausahawan. Upaya menumbuhkan minat wirausaha ini juga perlu difasilitasi dengan pemahaman kampus terkait karakter wirausaha mahasiswa, agar program kewirausahaan dapat dijalankan secara efektif dengan memperhatikan karakteristik pribadi mahasiswa. Studi ini bertujuan untuk menguji pengaruh trait kepribadian terhadap karakter wirausaha, dan menguji karakter wirausaha dalam memprediksi perilaku wirausaha pada lulusan Pendidikan tinggi di Indonesia. Studi ini diujikan menggunakan metode kuantitatif nonexperimental melalui survei pada 69 lulusan Pendidikan tinggi yang 42% berwirausaha. Karakter Wirausaha diujikan melalui 22 aitem Skala Karakter Wirausaha (Husna, Zahra & Haq, 2018), sedangkan trait kepribadian conscientiousness diujikan menggunakan alat ukur Ten Item Personality Inventory oleh Gosling versi Bahasa (Akhtar, 2018). Hasil studi menunjukkan bahwa karakter wirausaha dapat dijelaskan oleh trait kepribadian conscientiousness sebesar 22% secara signifikan (p≤0,05). Karakter wirausaha berhubungan dengan perilaku wirausaha dan karakteristik keluarga (memiliki orangtua berwirausaha) pada lulusan perguruan tinggi di Indonesia, namun faktor Pendidikan wirausaha tidak signifikan berhubungan dengan karakter wirausaha. Studi lanjutan disarankan untuk menguji lebih lanjut tentang Pendidikan kewirausahaan dalam memprediksi perilaku wirausaha dan efektivitas Pendidikan kewirausahaan dalam menumbuhkan minat dan perilaku wirausaha.